Akibat Hukum Pelaksanaan Petunjuk Jaksa Yang Dilakukan Oleh Jaksa Terhadap Pasal 385 KUHP - Arief Pratomo (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Land is very human life so it is not surprising that every human being wants to possess or control it which results in various land problems or land conflicts in Indonesia. These land issues sometimes also lead to crimes against land which can often lead to disputes between individuals. This is more due to the availability of land that is available and limited in number is not comparable to human needs, the more days the higher the value of fulfillment of land use. The research conducted was descriptive research with normative legal approach method (normative juridical) carried out by means of literature study. The data collection tool used in this study is data in the form of document studies and literature searches. The theory used in this research is the theory of Criminal Liability, Theory of Legal Certainty and Justice Theory. Based on the results of the study it was understood that the basis for the issuance of the attorney's instructions or policies on the prosecutor's institution was Law No. 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia and the Criminal Procedure Code contained in article 110.